2018
DOI: 10.3390/ijerph15112342
|View full text |Cite
|
Sign up to set email alerts
|

Summary Outcomes of the ODIN Project on Food Fortification for Vitamin D Deficiency Prevention

Abstract: Food-based solutions for optimal vitamin D nutrition and health through the life cycle (ODIN) was a cross-disciplinary, collaborative project, including 30 partners from 19 countries, which aimed to develop evidence-based solutions to prevent low vitamin D status (25-hydroxyvitamin D (25(OH)D) < 30 nmol/L) using a food-first approach. This paper provides a summary overview of some of the important ODIN outcomes and outlines some outstanding data requirements. In a study of almost 56,000 individuals, the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 53 publications
2
48
0
Order By: Relevance
“…Several studies conducted in Europe and around the world have shown substantial vitamin D insufficiency and deficiency among different population groups [1][2][3][4][5][6][7][8]. Due to the many roles of vitamin D in human physiology, its low serum concentrations can pose a health risk [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in Europe and around the world have shown substantial vitamin D insufficiency and deficiency among different population groups [1][2][3][4][5][6][7][8]. Due to the many roles of vitamin D in human physiology, its low serum concentrations can pose a health risk [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…In September 2019, a Forum was convened, with funding from the Rank Prize Funds, to explore the current situation and options for implementation strategies for increasing vitamin D intake across the distribution of food consumption patterns in the UK. The Forum discussed the potential of food fortification as a strategy, using learnings from the pan‐European ODIN study (Kiely & Cashman 2015; Kiely & Cashman 2018). Since the Forum took place, the coronavirus pandemic has placed a spotlight on the potential of good nutrition to promote immune function (https://www.nutrition.org.uk/healthyliving/helpingyoueatwell/covid19immunity.html) and, in this context, the association between low vitamin D status and reduced immune response has been flagged.…”
Section: April To September October To Marchmentioning
confidence: 99%
“…Animal‐feeding trials with added vitamin D in the animals' diets ( e.g. to biofortify meat or eggs), food production studies and data from dose–response and dietary modelling studies indicate that dairy products, bread, meats and hens’ eggs could be viable fortification vehicles and that diverse fortification strategies could increase vitamin D intake across the distribution of population intakes and hence reduce the risk of deficiency (Kiely & Cashman 2018). Vitamin D 3 is considered more effective than vitamin D 2 for raising plasma 25(OH)D concentrations, which has implications for choice of fortificant (Tripkovic et al 2012; Tripkovic et al 2017).…”
Section: Options For Increasing Vitamin D Intakementioning
confidence: 99%
“…Moreover, VD was reported to have pleiotropic effects such as regulation of immunological system [8,9], effects on the cardiovascular system via the renin-angiotensin-aldosterone system [10,11], and regulation of insulin secretion [12][13][14]. In some countries, food is fortified for VD [15]. For instance, in Poland margarine is fortified for VD.…”
Section: Introductionmentioning
confidence: 99%